The role of high-dose myeloablative chemotherapy with haematopoietic stem cell transplantation (HSCT) in children with central nervous system (CNS) tumours: protocol for a systematic review and meta-analysis. Issue 1 (December 2015) - Main, Caroline; Wilson, Jayne; Stevens, Simon; Houlton, Aimee; English, Martin; Kearns, Pamela; Phillips, Bob; Pizer, Barry; Wilne, Sophie; Wheatley, Keith
Abstract Objectives The objective of the study is to conduct a systematic review to compare the effects of high-dose chemotherapy (HDCT) with autologous haematopoietic stem cell transplantation (HSCT) versus standard-dose chemotherapy (SDCT) in children with malignant central nervous system (CNS) tumours. Methods Standard systematic review methods aimed at minimising bias will be employed for study identification, selection and data extraction. Ten electronic databases will be searched, along with citation searching and reference checking. Studies assessing the effects of HDCT with HSCT in children with CNS tumours will be included. The outcomes are survival (overall, progression-free, event-free, disease-free), response rates, short- and long-term adverse events and health-related quality of life (HRQoL). Two reviewers will independently screen and select randomised and non-randomised controlled trials and controlled and uncontrolled observational studies for inclusion. Quality assessment will be tailored to the different study designs. Where possible data will be summarised using combined estimates of effect for the hazard ratio for survival outcomes and the risk ratio for response rates. A fixed effect model will be used; sub-group analyses and meta-regression will be used to explore potential sources of heterogeneity between studies. Discussion Given the poor prognosis of malignant brain tumours in children in terms of survival and quality of life, this review will help guide clinical practice by summarising the current evidence on the use of high-dose myeloblative chemotherapy with stem cell support in children with CNS tumours.